Interest and satisfaction of dentists in practicing periodontics: A survey based on treatment of gingival recession - Vishakha Grover; Anoop Kapoor; Ranjan Malhotra; Sonia Sachdeva (Wolters Kluwer Medknow Publications, 2012)
Background: Gingival recession is a common occurrence and patients often report to dental clinic with associated problems such as root surface hypersensitivity, esthetic concerns, cervical root abrasions, and root caries that make it a concern for patients. Based upon the fact that gingival recession is an enigma for clinicians because of multitude of etiological factors and plethora of treatment modalities present for its treatment, a survey was conducted to assess knowledge as well as opinion about most common etiology, classification, and preferred treatment of gingival recession and to evaluate the interest and satisfaction of dentists in practicing periodontics. Materials and Methods: Study design consisted of a cross-sectional online survey, conducted among dentists practicing in state of Punjab, India, in the month of April 2011. A structured online questionnaire consisting of 17 questions evaluating the interest of dentists in periodontics based on knowledge about gingival recession (most of them giving the possibility of multiple choices of answers) was sent to about 300 dentists. Pearson Chi-Square and Mann-Whitney U tests were used for statistical analysis of data collected. P ≤ 0.05 was considered as statistically significant and P ≤ 0.01 considered as highly significant. Results: A greater proportion of periodontists had better knowledge about etiology (P = 0.07), classification (P = 0.000), and treatment of gingival recession (P = 0.000). A greater number of periodontists opted for the surgical modalities to correct the defects produced by gingival recession as compared to non-periodontists and had better interest (P = 0.000) and satisfaction (P = 0.000) in practicing periodontics. Conclusion: The results elucidated that periodontists had better interest and satisfaction in practicing periodontics, and were more inclined towards surgical correction of gingival recession as compared to non-periodontists.